Potential downside effects of Basel III : lessons from previous Accords. - Wood, Christopher (My University, 2014)
The Basel III accord is the cornerstone of global financial reform efforts that seek to guard against the types of financial crisis seen in 2007/8. It requires banks to fund more of their activities with better-quality capital and, in so doing, attempts to assure that they are better able to absorb shocks that can lead to crises. However, capital requirements come with a range of costs, which could spark a slowdown in credit or a change in the types of lending banks engage in. This paper conducts a comprehensive literature review of theoretical and empirical studies of the impacts of previous Accords, Basel I and Basel II, and attempts to draw lessons on possible downside effects of the latest iteration of the Basel Accord. It proceeds in three parts. Part 1 explores the history of the Basel Accords, exploring their theoretical basis and the evolution of the regulation into its current form. This section identifies two possible mechanisms by which capital regulation can negatively impact the broader economy: increasing capital costs and increasing risk aversion. Part 2 explores the potential for increased capital cost, while Part 3 examines the possibility of excessive risk aversion. In conclusion, the paper finds that while the potential for downside effects does exist, these are not likely to be significant, and seem particularly unlikely to have a major impact in the South African case.
Keywords: Basel III; Basel Accords; Financial crises; Banks and banking